2022
DOI: 10.1002/ejic.202100904
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Structure‐Property Relationships towards Multi‐Dimensional Applications of a Paddle‐Wheel Cu(II) Compound

Abstract: Dedicated to Professor Chittaranjan Sinha on the occasion of his 61st birthdayThe systematic understanding of structure-property correlations of coordination compounds can be utilized for their potential applications. To rationalize this concept, a mixed ligand based Cu(II) compound [Cu 2 (nac) 4 (4-nvp) 2 ](1) (Hnac = 3-(1naphthyl)acrylic acid and 4-nvp = 4-(1-naphthylvinyl)pyridine) has been synthesized and single crystal is obtained by the simple layering technique. Compound 1 has fascinating paddle wheel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Normally, carboxylate-bridging ligands would not conduct electricity due to the presence of insulating C-centers while the presence of metal (even diamagnetic) knots controls the energy difference between valence and conduction bands and make them helpful for electrical communicators and/or semiconductors. In the past few years, it has been explored that CPs are working as better electrical conductors and storage systems than conventional electrical devices. Some excellent porous conducting polymers (PCPs) of Zn­(II), Cd­(II), and few other transition metal ions are reported recently. To the best of our knowledge, Mn­(II)-based CPs are still rare in the literature for serving as electrical conductors. It is assumed that d 5 high-spin electronic configuration of Mn­(II) having the highest magnetic field may accelerate the electronic properties of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, carboxylate-bridging ligands would not conduct electricity due to the presence of insulating C-centers while the presence of metal (even diamagnetic) knots controls the energy difference between valence and conduction bands and make them helpful for electrical communicators and/or semiconductors. In the past few years, it has been explored that CPs are working as better electrical conductors and storage systems than conventional electrical devices. Some excellent porous conducting polymers (PCPs) of Zn­(II), Cd­(II), and few other transition metal ions are reported recently. To the best of our knowledge, Mn­(II)-based CPs are still rare in the literature for serving as electrical conductors. It is assumed that d 5 high-spin electronic configuration of Mn­(II) having the highest magnetic field may accelerate the electronic properties of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…Dinuclear copper (II) complexes that can mimic the structural or/and the functional aspect of catechol oxidase are well reported in literature [13][14][15][16][17][18]. From the literature review it is observed that the Cu(II) based paddle wheel complexes having different catalytic activities are well known [19][20], however, having catecholase activity of such type of complexes are still rare [21].…”
Section: Introductionmentioning
confidence: 99%
“…Design and research of transition metal complexes have attracted increasing attention in recent years because of their essential roles in catalysis, materials chemistry, photophysics, and bioinorganic chemistry. Understanding of metal complexes originated from the pioneer discovery of Alfred Werner regarding the spatial arrangement of metal complexes, which is directly related to their observed properties. Although a duration of more than a century is over, the crystal engineering of metal complexes is still continuing to undergo rapid expansion. However, metal complexes have the possibility of involving supramolecular interactions to generate infinite one-dimensional (1D), two-dimensional (2D), or three-dimensional (3D) network structures. These interactions include hydrogen bonding, halogen bonding, and π···π and C–H···π interactions. The most popular and successful approaches to fabricate supramolecular aggregates are using hydrogen bonding and π···π stacking interactions. , Organic ligands with an extended π-functionality have additional sites for interacting with π-ligands in an array. , …”
Section: Introductionmentioning
confidence: 99%